As in Forests, So in Verse: Clearings and the Poetics of Lack in Finnish Forest Poetry - Karoliina Lummaa (Literature, 2023)
Forests and forestry have been recurrent topics in Finnish environmental poetry since the 1970s, reflecting the importance of the cultural meanings of forests and forest-related livelihoods in Finland. Despite the recent forest boom in Finnish contemporary art and literature, contemporary sylvan poetics in Finnish poetry has remained an understudied topic. Moreover, the wider ecocritical discussions on the artistic and poetic dimensions of forest management and economy are still scarce, at least in the Nordic cultural context. To ignite these discussions, this study examines the meanings of forest clearings in contemporary Finnish poetry. Theoretically, this study draws from ecocriticism, with a particular emphasis on ecopoetics. By focusing on typography, rhetorics and thematics, this article shows how forest poems written by Jouni Tossavainen, Janette Hannukainen and Mikael Brygger combine technical forestry terminology with affective language and visual means to express anthropogenic changes in forests, resulting in a specific expressive style conceptualised as the poetics of lack. This poetics consists of ideas and rhetorical and typographical elements that together denote and express a variety of experiences, emotions and thoughts regarding a lack of trees, as well as a lack of natural organisation in forest growth.